Clinical implementation of pencil beam scanning proton therapy for liver cancer with forced deep expiration breath hold. (January 2021) - Fracchiolla, Francesco; Dionisi, Francesco; Righetto, Roberto; Widesott, Lamberto; Giacomelli, Irene; Cartechini, Giorgio; Farace, Paolo; Bertolini, Mattia; Amichetti, Maurizio; Schwarz, Marco
Highlights: Clinical implementation of breath-hold treatment technique for liver cancer with PBS. Interplay effects, setup and range uncertainties impact were assessed for 17 plans. Inter- and intra-breath hold liver position reproducibility were evaluated. Abstract: Purpose: To present our technique for liver cancer treatments with proton therapy in pencil beam scanning mode and to evaluate the impact of uncertainties on plan quality. Materials and Methods: Seventeen patients affected by liver cancer were included in this study. Patients were imaged and treated in forced breath-hold using the Active Breathing Coordinator system and monitored with an optical tracking system. Three simulation CTs were acquired to estimate the anatomical variability between breath-holds and generate an internal target volume (ITV). The treatment plans were optimized with a Single Field Optimization technique aimed at minimizing the use of range shifter. Plan robustness was tested simulating systematic range and setup uncertainties, as well as the interplay effect between breath-holds. The appropriateness of margin was further verified based on the actual positioning data acquired during treatment. Results: The dose distributions of the nominal plans achieved a satisfactory target coverage in 11 out of 17 patients, while in the remaining 6 D95 to the PTV was affected by the constraint on mean liver dose. The constraints for all other organs at risk were always within tolerances. The interplay effect had a limited impact on the dose distributions: the worst case scenario showed a D95 reduction in the ITV < 3.9 GyRBE and no OAR with D1  > 105% of the prescription dose. The robustness analysis showed that for 13 out of 17 patients the ITV coverage in terms of D95 was better than D95 of the PTV in the nominal plan. For the remaining 4 patients, the maximum difference between ITV D95 and PTV D95 was ≤0.7% even for the largest simulated setup error and it was deemed clinically acceptable. Hot spots in the OARs were always lower than 105% of the prescription dose. Positioning images confirmed that the breath hold technique and the PTV margin were adequate to compensate for inter- and intra-breath-hold variations in liver position. Conclusion: We designed and clinically applied a technique for the treatment of liver cancer with proton pencil beam scanning in forced deep expiration breath-hold. The initial data on plan robustness and patient positioning suggest that the choices in terms of planning technique and treatment margins are able to reach the desired balance between target coverage and organ at risk sparing.